Serum ferritin levels in previously untreated classical Hodgkin lymphoma: correlations and prognostic significance. Issue 4 (21st March 2022) - Karakatsanis, Stamatios; Panitsas, Fotios; Arapaki, Maria; Galopoulos, Dimitrios; Asimakopoulos, John V.; Liaskas, Athanassios; Chatzidimitriou, Chrysovalantou; Belia, Marina; Konstantinou, Elianna; Vassilopoulos, Ioannis; Papadatos, Stamatis S.; Sachanas, Sotirios; et al.
Abstract: Serum ferritin (SF) is frequently elevated in classical Hodgkin lymphoma (cHL). We report on its prognostic significance in an unselected series of 529 cHL patients treated with state-of-the-art therapy. Higher baseline levels correlated with markers of advanced/aggressive disease. SF levels were significantly higher in male and older patients, those with high body mass index and mixed cellularity histology. The strongest correlation was recorded between SF and complement reactive protein (CRP) levels. Gender-specific SF cutoffs which provided the best discrimination in terms of freedom from progression (FFP) were identified. In multivariate analysis elevated SF levels, advanced stage and high lactate dehydrogenase (LDH) were independent prognostic factors of inferior FFP. SF also appears to retain independent prognostic significance for progression-free survival (PFS) but not for overall survival (OS). In conclusion, SF levels in cHL reflect disease activity and are associated with adverse patient outcomes.